Sekolah Alam vs. Ki Hajar Dewantara: A Progressive Humanism Study - Iqbo, John (CV. Mitkom Indotama, 2023)
This study aimed to examine the parallels and distinctions between the Sekolah Alam methodology and Ki Hajar Dewantara's perspectives within the framework of progressive humanism. The significance of this research lay in identifying both the commonalities and differences in educational philosophies between Sekolah Alam and Ki Hajar Dewantara. Utilizing a meta-analysis approach, this investigation drew upon a variety of journals and books pertinent to the topic, with 12 journal articles sourced from Google Scholar forming the core data set. These sources were meticulously analyzed to extract comprehensive insights through a qualitative synthesis. The findings revealed notable similarities between the Sekolah Alam approach and Ki Hajar Dewantara's ideology, such as the emphasis on natural inclination in education, the objective of humanizing individuals, instilling moral values, leadership skills, logical thinking, entrepreneurship, and the inclusion of community and family in the educational process, all within a democratic, non-authoritarian framework. On the other hand, a key distinction emerged in that the Sekolah Alam philosophy is rooted in Quranic principles, viewing humans as stewards of the Earth accountable to the Creator, whereas Ki Hajar Dewantara's philosophy is grounded in local traditions, with a particular focus on accommodating students with special needs—a demographic that Sekolah Alam recognizes more prominently—and emphasizing education for minority groups, to which Ki Hajar Dewantara devoted more attention than Sekolah Alam.